Passive tracers in a general circulation model of the Southern Ocean - I. G. Stevens (Annales Geophysicae, 1999)
Passive tracers are used in an off-line version of the United Kingdom Fine Resolution Antarctic Model (FRAM) to highlight features of the circulation and provide information on the inter-ocean exchange of water masses. The use of passive tracers allows a picture to be built up of the deep circulation which is not readily apparent from examination of the velocity or density fields. Comparison of observations with FRAM results gives good agreement for many features of the Southern Ocean circulation. Tracer distributions are consistent with the concept of a global "conveyor belt" with a return path via the Agulhas retroflection region for the replenishment of North Atlantic Deep Water. Key words. Oceanography: general (numerical modeling; water masses) · Oceanography: physical (general circulation)